In vitro study of factors influencing the duration of antimicrobial protection of antimicrobial-impregnated external ventricular drains. (2nd December 2021) - Lang, Elodie; Hulin, Anne; Egbeola-Martial, Julia; Drouard, Leonard; Roujansky, Ariane; Tomberli, Françoise; Bardon, Jean; Schimpf, Caroline; Senova, Suhan; Cook, Fabrice; Lebeaux, David; Mounier, Roman
Abstract: Background: In vitro and clinical studies assessing the duration of the protective activity of antimicrobial-impregnated external ventricular drains (AI-EVDs) gave conflicting results. Objectives: To identify factors associated with decreased antimicrobial activity of AI-EVDs that were not taken into account in previous in vitro models. Methods: We performed in vitro experiments with Bactiseal™ AI-EVDs, under different conditions. Tested parameters were chosen to mimic conditions in which AI-EVDs are used: perfusion by saline (at different flow rates) or not perfused, dwelling medium (air, saline, saline+protein, lipid) and temperature. Antimicrobial activity was assessed by measurement of inhibitory diameters of a 0.5 cm portion of an AI-EVD (cut every 2 days) placed onto agar plates covered by a standardized Staphylococcus spp. inoculum (three different isolates). MS was used to measure concentrations of rifampicin and clindamycin after 48 h of dwelling. Results: In univariate analysis, most of the tested factors were associated with reduced antimicrobial activity: liquid media (as compared with ambient air), perfusion whatever the rate flow (as compared with no perfusion) and presence of protein in the media. In multivariate analysis, dwelling in media (lipid or saline) was the most constantly associated with a reduction of inhibition diameters ( P < 0.01), as compared with ambient air. After 48 h of dwelling, the clindamycin concentration was higher than 100 and 450 mg/L in saline and saline+BSA, respectively. Conclusions: The medium in which an AI-EVD is dwelling plays a significant role in the duration of AI-EVD activity. These results may explain conflicting results between clinical and in vitro studies.